Health reform in Mexico: governance and potential outcomes - Jorge L. León-Cortés; Gustavo Leal Fernández; Héctor J. Sánchez-Pérez (BMC, 2019)
Abstract Adopting key mechanisms to restructure public policy in developing countries is a crucial political task. The strengthening of infrastructure of health services, care quality, monitoring and population health; all might contribute to assuring the functionality of a national system for health monitoring and care. Over the last decades, the Mexican government has launched wide-ranging political reforms aiming to overcome socioeconomic and environmental problems, namely health, education, finances, energy and pension. The proposed (but yet not implemented) health reform in Mexico during E. Peña Nieto's administration (2012-2018) pretended an adjustment in Article 4 of the Mexican Constitution to compact medical care and reduce the State's responsibility to a provision of minimum health packages for the population. Here we use a simple analytical model to describe and interprete the concepts of context, process, actors and content and the outcome of three of the most important resulting components of this intended reform i.e. universality, basic packages, and 'outsourcing'. In light of the start of the Mexico's new federal administration, we argue that, if not properly defined by all actors, the implementation of such structural health reform in Mexico would precipitate a model of private/public association exacerbating a crisis of political representation, human rights, justice and governance.